Guidelines on the surgical management of sleep disorders: A systematic review. (1st May 2019) - Mandavia, Rishi; Mehta, Nishchay; Veer, Vik
Abstract : Objective: To facilitate the development of U.K. guidelines for sleep surgery and to guide sleep surgeons to existing guidelines relevant to their practice, we provide a systematic review and quality assessment of all existing guidelines on the surgical management of sleep disorders. Methods: Systematic review using preferred reporting items for systematic reviews and meta‐analyses (PRISMA) recommendations. Medline and Embase databases were searched from inception to April 2018. Publications were included if they described a guideline for the surgical management of sleep disorders. Three assessors used the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument to evaluate included guidelines. Results: The systematic search revealed 1, 161 publications. Twenty‐two guidelines from eight countries were included. Fourteen focused on adults, five on children, and three on both. The guidelines discussed nasal, tonsillar, palatal, tongue, hyoid, maxillomandibular, tracheal, bariatric, and multilevel surgeries. The mean overall AGREE II quality score of included guidelines was 3.5 (range = 2 to 5.3; maximum possible score = 7). Conclusion: This article provides a summary and quality assessment of all published guidelines on the surgical management of sleep disorders. No U.K. guidelines were identified, and existing guidelines have several shortcomings. This highlights the need for robust U.K. national guidelines on sleep surgery to promote clinical and cost‐effective care in this field. Our findings can be used by stakeholders as a foundation for the development of new guidelines and can be used by sleep surgeons to direct them to existing guidelines relevant to their practice, promoting evidence‐based clinical care. Laryngoscope, 130:1070–1084, 2020